The Model of Creative Thinking, Critical Thinking, and Entrepreneurial Skills Among University Students - Yanuarto, Wanda Nugroho; Hapsari, Ira (Universitas Muhammadiyah Mataram, 2022)
Digital skills for the twenty-first century are comprise of four fundamental capabilities: cognition abilities; process capabilities; systems capabilities; and social skills. Using one's ability to think creatively to demonstrate cognitive abilities can be very effective. On the other hand, critical thinking is a skill that can be developed at the university level and is used to transform raw data into meaningful information. Furthermore, the study purpose is investigate the relationship the entrepreneurial skills in students in the world of education, both in terms of educational and economic issues. Researchers are looking into the relative importance of creative thinking (CRE), critical thinking (CRI), and entrepreneurial skills (ETS) as primary predictors of success when it comes to learning and mastering skills in the technologically advanced development society (TCDS). In this study, which takes a quantitative approach, a cross-sectional survey gathers data. In order to analyze the relationship formed by CRE, CRI, and ETS among university students in TCDS, we used the structural equation model (SEM) method. In this study, 85 students from the Faculty of Teacher Training and Education, and 315 students from the Faculty of Economics and Business at Universitas Muhammadiyah Purwokerto participated, for a total of 315 students. The following research procedures were used in this investigation: (3) The relationship between CRE, CRI, and ETS was determined using a Structural Equation Model (SEM). In addition, the findings of this study include the following points: The EFA and CFA analysis revealed that the CRE construct contained four valid sub-constructs, while the CRI and ETS constructs each contained five valid sub-constructs. The results of the SEM analysis revealed a statistically significant relationship between CRE, CRI, and ETS, with a moderately significant relationship between CRE and ETS ( = 0,291), as well as a statistically significant relationship between CRI and ETS ( = 0,143). The correlation between CRE and CRI, on the other hand, was found to be high ( = 0.894). Finally, demonstrate that the CRE, CRI, and ETS have played a role in improving the performance of university students during the TCDS era.